Kieślowski Re-read: On Reality, Realism and Cinema - Parmeggiani, Francesca (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
By referencing Italian auteurs Ermanno Olmi and Federico Fellini, this paper offers a re-reading of Krzysztof Kieślowski’s reflections on cinema that places the practice of describing reality and uttering “a statement of fact” about people’s lives and the world as a long-lasting, structuring foundation of his episteme and workshop.